Dampak Pemekaran Terhadap Pelayanan Kesehatan di Dinas Kesehatan Kabupaten Lamandau = Impact of the Regional Extension on the Health Service at the Health Department of Lamandau Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
This research is conducted to find out and to examine to impact of the regional extension on the health services in the Health Departement of Lamandau Regency. The analytical method employed in this research is descriptive-qualitative, done by summarizing or reducing the data, presenting the data, and drawing the conclusion. This study uses evaluation research with formative method, where the program that will be observed has been on for two years, and then comparing between the conditions before and after the regional extension occurred. Meanwhile, the data gathering technique is done through observation, interview, and documentation. It can be concluded that the impact of the regional extension on the health departement organizations, expecially on its structures of organization, human resources, and organizational cultures has not yielded a significant change. This has an impact on the success of the health services for the society. From its accessibility, there have been many improvements after the extension. People are getting easier to obtain lower cost of health services along with more extensive time and means of transportations. From its effec- tiveness, the impact has been sufficient enough. However, from its responsiveness there is a lack of responses by service providers to the complaints from society. In order to enhance the health service to its optimum level, some steps need to be taken. First, by evaluating the performance of the health department that has been going on for nearly two years now for the purpose that regional extension could bring significant changes to the health develop- ment in Larnandau Regency. Second, by applying standardized service to ensure the existence of the optimum health services. Third, by recruiting qualified human resources in accordance with the formation needed so that the services could be carried out optimally. Fourth, by giving easier access for the society so thet they could easily access all of the services.